2007
DOI: 10.1055/s-2007-979393
|View full text |Cite
|
Sign up to set email alerts
|

Lungenkarzinom: Diagnostik und Staging

Abstract: Despite medical advances lung cancer remains the leading cause of cancer deaths. Lung cancer is usually recognized late in its natural history and at presentation in 80 % unresectable. Smoking history is the most important risk factor. At present time, screening for lung cancer is not recommended. The only chance for cure is tumour resection in early stages, performed in about 20 % of all lung cancer cases. Histological subtypes are non-small cell lung cancer (NSCLC) (80 % of lung cancers) and 20 % small cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Small cell lung cancer, as a pathological type with high malignancy and invasiveness in lung cancer, the gold standard for diagnosis is to obtain cytology or histology for pathological diagnosis. 29 , 30 Even in early stages of lung cancer, it is necessary to diagnose small cell lung cancer by obtaining a small quantity of cytological specimens, which can already been observed tumor lesions on CT or PET-CT. The advantage of this study is that cancer cells with a very small quantity of cells can be identified through probes, even if they are not demonstrated in imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Small cell lung cancer, as a pathological type with high malignancy and invasiveness in lung cancer, the gold standard for diagnosis is to obtain cytology or histology for pathological diagnosis. 29 , 30 Even in early stages of lung cancer, it is necessary to diagnose small cell lung cancer by obtaining a small quantity of cytological specimens, which can already been observed tumor lesions on CT or PET-CT. The advantage of this study is that cancer cells with a very small quantity of cells can be identified through probes, even if they are not demonstrated in imaging.…”
Section: Discussionmentioning
confidence: 99%